2022
DOI: 10.3390/ijerph19042029
|View full text |Cite
|
Sign up to set email alerts
|

Potential Toxic Effects of Exposure to Titanium Silicon Oxide Nanoparticles in Male Rats

Abstract: . Recently, nano titanium silicon oxide (TiSiO4 NPs) has been used in different fields and industries. Very few toxicological data exist for TiSiO4 NPs. In the present study, the potential adverse effects of oral exposure to a single dose of TiSiO4 NPs ≤50 nm (250 mg/kg b.w.) in adult male rats were investigated through the assessment of biomarkers for serum biochemical parameters, liver DNA damage, and histopathological examination and determination of Si and Ti in the exposed rat tissues. The results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The findings presented here agree with previous studies shown that TiO 2 -NPs induced elevation of apoptotic and oxidative stress genes in liver and intestine tissues in rat after 7 days of administration 41 , 42 . It has concluded that the large surface area of TiO 2 -NPs caused an increased production of reactive oxygen species which resulted in imbalanced homeostasis between oxidation and anti-oxidative activities that implicated with the oxidative stress, genotoxicity and cytotoxicity 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented here agree with previous studies shown that TiO 2 -NPs induced elevation of apoptotic and oxidative stress genes in liver and intestine tissues in rat after 7 days of administration 41 , 42 . It has concluded that the large surface area of TiO 2 -NPs caused an increased production of reactive oxygen species which resulted in imbalanced homeostasis between oxidation and anti-oxidative activities that implicated with the oxidative stress, genotoxicity and cytotoxicity 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MDA, SOD, GSH, GSH-Px, and T-AOC are the indications of oxidative stress, and they were also significantly changed by nano-TiO 2 in the mice. Nano-TiO 2 is recognized as prooxidant that induces ROS generation, consequently causing inflammation, apoptosis, and cell damage (Ghareeb et al, 2022) (Abbasi-Oshaghi et al, 2019). GSH is involved in scavenging ROS and protecting the body from oxidative injury.…”
Section: Discussionmentioning
confidence: 99%
“…Gpx enzymes convert lipid hydroperoxides to alcohols and convert the free hydrogen peroxide to water [42]. Several investigators have reported that nano-TiO2 upregulate mRNA expression of oxidative-stress-related genes, induce oxidative DNA damage and thus, production of intracellular reactive oxygen species in various cell types was recorded [16,18,43].It has been concluded that the large surface area of nanoparticles causes an increase in the production of ROS, leading to an imbalance between oxidation and anti-oxidation, which causes oxidative stress, genotoxicity, and hepatotoxicity [23,44].…”
Section: Discussionmentioning
confidence: 99%